Programa Dramatifábulas con títeres para mejorar la práctica de los valores de respeto y solidaridad en niños de 5 años de la I.E. N° 211, 2019 - Cusquipoma Vega, Yuly Analí (2021)
This research entitled Dramatifabulas program with puppets to improve the practice the values _x000D_ of respect and solidarity in 5 year old children of the I.E. N°211, 2019, had the purpose of _x000D_ addressing the problem presented by most of the students in the preschool age in the _x000D_ development of the values of respect and solidarity, through the application of a program based _x000D_ on dramatization with puppets, which in the end benefited the integral development of the child._x000D_ The research was applied with a pre-experimental design, with a single experimental group, _x000D_ with pre-test and post-test. Likewise, it was carried out with a sample of 24 boys and girls from _x000D_ the 5 year old classroom section "A" of I.E. 211._x000D_ The results obtained in the pre-test showed that 70.83% of the children were at a low level and _x000D_ 29.17% at a medium level with respect to respect and solidarity; but after applying the _x000D_ Dramatifabulas program, 83.33% obtained a high level and only 16.67% at a medium level. In _x000D_ addition, it was demonstrated that there was a significant difference of 2.12 average points in _x000D_ the improvement of respect and solidarity.